Describing the intersection of ethnicity and gender in early-stage non–small cell lung cancerCentral MessagePerspective - Hamza Rshaidat, MD; Isheeta Madeka, MD; Gregory L. Whitehorn, BS; Jonathan Martin, BS; Shale J. Mack, BS; Sneha Alaparthi, MD; Tyler R. Grenda, MD; Nathaniel R. Evans, III, MD; Olugbenga T. Okusanya, MD (JTCVS Open)
Objective: Female sex has been associated with improved survival after lung cancer resection. Our aim is to use a national database to describe sex disparities in early lung cancer treatment and evaluate whether outcomes of ethnic groups who traditionally have poorer outcomes are attenuated by female sex. Methods: This is a retrospective cohort study using the 2020 National Cancer Database. Adult patients diagnosed between 2010 and 2019 with early-stage non–small cell lung cancer (clinical T1 or T2, N0, M0) who received surgical resection with a known vital status were included. Patients who received neoadjuvant systemic or radiation therapy were excluded. Demographic data; clinicopathologic variables; 30-day, 90-day, 5-year mortality; and 5-year overall survival were analyzed. Results: We identified 192,927 patients with surgically resected early-stage non–small cell lung cancer. Mean patient age was 69 years (interquartile range, 62-75). Five-year overall survival among women was 72.8% versus 60.4% in men (P < .001), with the largest difference between Asian Pacific Islander women and men. Among women, White and Black women had the lowest 5-year overall survival. White and Black women had a higher 5-year overall survival than White, Black, Hispanic, and Other men. Conclusions: Female sex was associated with improved overall survival in patients with early-stage lung cancer regardless of ethnicity. However, there is significant variation between ethnic groups in the absolute size of this association. Additional studies are necessary to determine which factors contribute to this disparity, including but not limited to biological, clinical, and health-systems related.